Global sediment thickness data set updated for the Australian‐Antarctic Southern Ocean. (28th August 2013) - Whittaker, Joanne M.; Goncharov, Alexey; Williams, Simon E.; Müller, R. Dietmar; Leitchenkov, German
Abstract : [1] We present a new, 5 min sediment thickness grid for the Australian‐Antarctic region (60°E–155°E, 30°S–70°S). New seismic reflection and refraction data have been used to add detail to the conjugate Australian and Antarctic margins and intervening ocean floor where regional sediment thickness patterns were poorly known previously. On the margins, sediment thickness estimates were computed from velocity‐depth functions from sonobuoy/refraction velocity solutions ground‐truthed against seismic reflection data. For the Southeast Indian Ridge abyssal plains, sediment thickness contours from Geli et al. (2007) were used. The new regional minimum sediment thickness grid was combined with the global National Geophysical Data Center (NGDC) sediment grid to create an updated global grid. Even using the minimum estimates, sediment accumulations on the extended Australian and Antarctic continental margins are 2 km thicker across large regions and up to 9 km thicker in the Ceduna Basin compared to the global NGDC compilation of sediment thickness data. Key Points: Global minimum sediment thickness compilation updated for Australia Antarctica Sediment thicknesses computed from seismic reflection and refraction data Sediment thicknesses up to 9 km thicker than previously estimated